SCREENING OF POTENTIAL NEW SOLID FORMS OF VITAMIN B1 WITH VITAMIN B3 - MURESAN-POP, M.; PETRISOR, D. M.; SIMON, S. (Studia Universitatis Babeș-Bolyai Physica, 2019)
The present study aimed to obtain new solid forms between Vitamin B1 (thiamine hydrochloride) and Vitamin B3 (nicotinamide) following the mechanochemistry route. The samples prepared by grinding in different solvents, of thiamine hydrochloride with nicotinamide in 1:1 and 1:2 molar ratios were investigated by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The XRD and FTIR results point out that for the chosen ratios of components and for the aqueous ethanol solution and for ethyl acetate used as solvents, none solid forms were obtained, but only physical mixtures. For the sample with1:2 molar ratio of B1:B3, the FTIR analysis reveals very small changes of few absorption bands consisting in a weak shift towards higher wavenumbers, due to grinding process.